Changes of Meranti, Padauk, and Merbau Wood Lignin during the ThermoWood Process - Kačíková, Danica; Kubovský, Ivan; Gaff, Milan; Kačík, František (Polymers, 2021)
Thermal modification is an environmentally friendly process in which technological properties of wood are modified using thermal energy without adding chemicals, the result of which is a value-added product. Wood samples of three tropical wood species (meranti, padauk, and merbau) were thermally treated according to the ThermoWood process at various temperatures (160, 180, 210 °C) and changes in isolated lignin were evaluated by nitrobenzene oxidation (NBO), Fourier-transform infrared spectroscopy (FTIR), and size exclusion chromatography (SEC). New data on the lignins of the investigated wood species were obtained, e.g., syringyl to guaiacyl ratio values (S/G) were 1.21, 1.70, and 3.09, and molecular weights were approx. 8600, 4300, and 8300 g·mol-1 for meranti, padauk, and merbau, respectively. Higher temperatures cause a decrease of methoxyls and an increase in C=O groups. Simultaneous degradation and condensation reactions in lignin occur during thermal treatment, the latter prevailing at higher temperatures.
Keywords: merbau; meranti; padauk; wood lignin; thermal treatment